Who likes to engage in writing? - The role of children's beliefs and intrinsic value regarding leisure writing - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Educational Psychology, 2020)
While leisure writing may help children to acquire writing skills, it can also be considered as an inherently valuable cultural activity. This study explores how children’s beliefs may explain to what extent children are inclined to leisure writing and if there are any gender differences. Building on preliminary scale development work, we analysed data from 963 third-graders. Variables included (a) the intrinsic value attached to leisure writing (b) preceding behavioural, normative, and control beliefs related to these activities, and (c) the level of leisure writing. In a structural equation model, the preceding beliefs were applied as explanatory variables for the intrinsic value. Intrinsic value, in turn, explained a large proportion of variance in children’s leisure-writing activities. Gender differences in leisure writing were mediated by intrinsic value. Significance of intrinsic value and preceding beliefs regarding leisure-writing activities are discussed.<br
CRIS-Team WoS Importer:2020-07-17
Keywords: Elementary school students; intrinsic value; literacy; leisure writing